Nepal at the crossroads - Shrivastava, L. P. S. (New Delhi : Allied, 1996)
On foreign relations of Nepal and India.
Includes index.
Keywords: Nepal -- Foreign relations -- India; India -- Foreign relations -- Nepal; Nepal -- Politics and government